Defective sarcomere organization and reduced larval locomotion and fish survival in slow muscle heavy chain 1 (smyhc1) mutants. Issue 1 (1st December 2019) - Li, Siping; Wen, Haishen; Du, Shaojun
Abstract: Zebrafish skeletal muscles are broadly divided into slow‐twitch and fast‐twitch muscle fibers. The slow fibers, which express a slow fiber‐specific myosin heavy chain 1 (Smyhc1), are the first group of muscle fibers formed during myogenesis. To uncover Smyhc1 function in muscle growth, we generated three mutant alleles with reading frame shift mutations in the zebrafish smyhc1 gene using CRISPR. The mutants showed shortened sarcomeres with no thick filaments and M‐lines in slow fibers of the mutant embryos. However, the formation of slow muscle precursors and expression of other slow muscle genes were not affected and fast muscles appeared normal. The smyhc1 mutant embryos and larvae showed reduced locomotion and food intake. The mutant larvae exhibited increased lethality of incomplete penetrance. Approximately 2/5 of the homozygous mutants were viable and grew into reproductive adults. These adult mutants displayed a typical pattern of slow and fast muscle fiber distribution, and regained normal slow muscle formation. Together, our studies indicate that Smyhc1 is essential for myogenesis in embryonic slow muscles, and loss of Smyhc1 results in defective sarcomere assembly, reduces larval motility and fish survival, but has no visible impact on muscle growth in juvenile and adult zebrafish that escape the larval lethality.